Analysis of the current situation of agricultural foreign direct investment in China (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
With the deepening of economic globalization and the domestic reform and opening up process, coupled with thecontinuous acceleration of industrialization and urbanization, a series of problems related to national security, such asecological and environmental protection pressure, shortage of cultivated land resources and shortage of food supply, havebeen highlighted, and the foreign investment of China's agricultural enterprises is needed.By analyzing the micro data, wefind that state-owned agricultural enterprises prefer developing countries, while private enterprises prefer developedcountries, which put forward the problems existing in the current process of foreign direct investment of agriculturalenterprises and put forward relevant suggestions.